Aptamer-based nanotrains and nanoflowers as quinine delivery systems - Mengyuan Cao; Anthony Vial; Laetitia Minder; Aurore Guédin; Sébastien Fribourg; Laurent Azéma; Cécile Feuillie; Michael Molinari; Carmelo Di Primo; Philippe Barthélémy; Leblond Chain Jeanne (International Journal of Pharmaceutics: X, 2023)
In this study, we designed aptamer-based self-assemblies for the delivery of quinine. Two different architectures were designed by hybridizing quinine binding aptamers and aptamers targeting Plasmodium falciparum lactate dehydrogenase (PfLDH): nanotrains and nanoflowers. Nanotrains consisted in controlled assembly of quinine binding aptamers through base-pairing linkers. Nanoflowers were larger assemblies obtained by Rolling Cycle Amplification of a quinine binding aptamer template. Self-assembly was confirmed by PAGE, AFM and cryoSEM. The nanotrains preserved their affinity for quinine and exhibited a higher drug selectivity than nanoflowers. Both demonstrated serum stability, hemocompatibility, low cytotoxicity or caspase activity but nanotrains were better tolerated than nanoflowers in the presence of quinine. Flanked with locomotive aptamers, the nanotrains maintained their targeting ability to the protein PfLDH as analyzed by EMSA and SPR experiments. To summarize, nanoflowers were large assemblies with high drug loading ability, but their gelating and aggregating properties prevent from precise characterization and impaired the cell viability in the presence of quinine. On the other hand, nanotrains were assembled in a selective way. They retain their affinity and specificity for the drug quinine, and their safety profile as well as their targeting ability hold promise for their use as drug delivery systems.